Application of the Roleplay Method to Improve Indonesian Language Learning Outcomes in Grade 4 Students of SDN Keleyan 1. - Farid Azka Alfikri; Dimas Sesario Alamsyah; Ryan Irfan Nuruddin; Fanny Rahmawan; Ahmad Hasbi Ashidiqi; Agung Setyawan (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2026)
This study aimed to improve the Indonesian language learning outcomes of 21 fourth-grade students at SDN Keleyan 1 through the roleplay method. It also sought to enhance students' understanding of character emotional changes, self-confidence, and learning concentration. The research employed a two-cycle Classroom Action Research (CAR) design involving planning, implementation, observation, and reflection. Data were collected through written tests, observations, and documentation and analyzed using quantitative and qualitative descriptive methods. The results showed that the roleplay method effectively improved students' learning outcomes, with the average score increasing from 82 in Cycle I to 84 in Cycle II and achieving 100% classical mastery. Students' self-confidence improved from sufficient (score 2) to excellent (score 4), while learning concentration increased from poor (score 1) to excellent (score 3). In conclusion, the roleplay method effectively enhances students' learning outcomes, confidence, and concentration, making it a valuable interactive approach for elementary classroom learning.